Preliminary Results of Conformal Computed Tomography (CT)-based Intracavitary Brachytherapy (ICBT) for Locally Advanced Cervical Cancer: A Single Institution's Experience - Ekkasit Tharavichitkul (2018)
Intracavitary brachytherapy using tandem and ovoids is an important component of definitive treatment for cervical cancer. In the present study, we analyzed the dose-volume histograms (DVHs) of the tumor volume and organs at risk including the sigmoid colon by CT-based treatment planning for high dose rate (HDR) intracavitary brachytherapy (ICBT) in cervical cancer. Seventeen patients with carcinoma of the cervix uteri were treated with external beam radiotherapy plus concurrent chemotherapy. For brachytherapy, the planning procedure started by performing a conventional plan which prescribed a dose of 6.5-7 Gy per fraction to point A, then optimized the dose based on CT imaging. Volumes and DVHs were calculated for the HR-CTV, bladder, rectum and sigmoid colon. The mean BED 2Gy total doses of post-optimized plans of HR-CTV, bladder, rectum and sigmoid colon were: 89.6, 94.1, 74.0 and 69.8 Gy, respectively. For conventional plans, the calculated mean BED 2Gy total doses of HR-CTV, bladder, rectum and sigmoid colon were 92.2, 120.1, 75.7 and 78.3 Gy, respectively. This study showed statistical significant higher BED 2Gy total doses for bladder and sigmoid colon (p < 0.001) using conventional plans versus post-optimized, CT-based plans, while no difference between HR-CTV and rectum BED 2Gy total doses could be detected. After a median follow-up of nineteen months, all seventeen patients had a clinical complete response. Two patients developed distant metastasis. Compared with conventional treatment, CT based brachytherapy planning was very effective in reducing doses to OARs, especially bladder and sigmoid colon whilst maintaining a high therapeutic dose for tumor target volumes in the treatment of cervical carcinoma.